FRI0460 Normal Patterns of Nailfold Videocapillaroscopy in Healthy Children and Adolescents Based on Different Age Ranges. (9th June 2015) - Piotto, D.G.P.; Sekiyama, J.; Kayser, C.; Yamada, M.; Len, C.; Terreri, M.T.
Abstract : Background: Videocapillaroscopy (NVC) is a safe, non-invasive, and cost-effective tool useful in the detection of individuals who are at risk for developing autoimmune rheumatic diseases (ARDs). However, few studies have assessed the use of NVC in the pediatric population. Objectives: 1. to describe the normal patterns of NVC in healthy children and adolescents in different age groups; 2. to quantify the linear relationship between the age and the capillary dimensions, intercapillary distance and number of capillaries/mm; 3. to evaluate the inter and intraobserver concordance in capillary measurements. Methods: This was a cross-sectional study including 100 healthy participants aged 5 to 18 years. NVC was performed using the stereomicroscope under 100x magnification. The capillary dimensions (capillary loop length, capillary width and intercapillary distance) and the number of capillaries/mm were evaluated. Three consecutive images were acquired in nine capillaries per individual, totalizing 900 capillaries examined and photographed. Four age groups were studied: 5-7 years (17); 8-10 years (24); 11-14 years (30) and 15-18 years (29). The intra and inter observer agreement were tested in 25% of subjects. Results: The capillary dimensions (mean ± SD) were: capillary loop length 278.6±60.3 μm, intercapillary distance 124.1±28.1 μm, capillary width 15.0±2.6 μm. The intercapillary distance was higher in girls (p=0.011). The intercapillary distance remained constant over time (p=0.088). Teenagers between 15 and 18 years had longer (318.7±64.4 μm) and more enlarged (16.2±3.3 μm) capillaries when compared to other age groups (p<0.001 and p=0.012 respectively). There was a significant increase in the number of capillaries/mm with age: 6.1 capillaries/mm (5-7 years); 7.0 (8 to 10 years); 8.0 (11-14 years) and 9.3 (15-18 years) (p<0.001). Additionally, there was a positive correlation between age and the number of capillaries/mm, capillary length, and capillary width (p<0.001, R=0.796; p<0.001, R=0.368; p=0.004, R=0.285, respectively). There was a good intra and interobserver concordance in all capillary measurements. Morphological abnormalities including enlarged capillary (capillary width percentile>97.5) and avascular areas (intercapillary distance percentile>97.5) were present in 11% and 10% of the capillaries respectively. A weak negative correlation was found between the intercapillary distance and the number of capillaries/mm (p=0.05; R=-0.20). Conclusions: There is a wide variability in the capillary morphology among healthy individuals. There was a positive correlation between age and the number of capillaries/mm, capillary length, and capillary width. There was a significant difference in the capillary length and width between the older and younger participants. In addition, NVC has been showed to be a reproducible method. References: Cutolo M, Suli A, Smith V. How to perform and interpret capillaroscopy. Best Pract Res Clin Rheumatol. 2013; 27:237-48. Ingegnoli F, Herrick AL. Nailfold capillaroscopy in pediatrics. Arthritis Care Res. 2013;65:1393-00. Herrick AL, Moore T, Hollis S, Jayson MI. The influence of age on nailfold capillary dimensions in childhood. J Rheumatol. 2000;27:797-00. Disclosure of Interest: None declared